2007
DOI: 10.1094/cm-2007-0927-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Optimum Adaptation Zones for Soybean Maturity Groups in the USA

Abstract: Soybean cultivars are generally adapted within a narrow north‐south geographical zone for full‐season growth due primarily to photoperiod response. The areas of adaptation were empirically defined more than three decades ago and re‐examination is needed. The accuracy of adaptation area determination can be improved by utilizing updated information, including changes in production practices and new technologies. The objective of this paper was to use current soybean yield data from experiments conducted across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 29 publications
(47 reference statements)
7
93
1
1
Order By: Relevance
“…These results are somewhat similar to Zhang et al (2007) who reported that MG 0 or earlier are better suited North of latitude 46°N including northern Wisconsin and Michigan using a different dataset (139 sites). Results from our study suggest that MG 0 should be restricted to North Dakota and northern Minnesota.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These results are somewhat similar to Zhang et al (2007) who reported that MG 0 or earlier are better suited North of latitude 46°N including northern Wisconsin and Michigan using a different dataset (139 sites). Results from our study suggest that MG 0 should be restricted to North Dakota and northern Minnesota.…”
Section: Resultssupporting
confidence: 90%
“…Results from our study suggest that MG 0 should be restricted to North Dakota and northern Minnesota. Also, Zhang et al (2007) used convex parallel lines to delineate optimum MG regions and they continued the lines to the western regions of the High Plains states (North and South Dakota) where there was a lack of trial data. Our updated map uses vastly more data, different methodology in data analysis, and extends the trial locations beyond those Zhang et al (2007) used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivar AC Bravor belongs to Maturity Group (MG) 0 and AC Harmony to MG 00. Based on the characteristics of the timing of flowering and maturity and its geographical adaptation, soybean has been classified into 13 MG from 000, 00, 0, 1… to 10 with an increasing life cycle (Cober and Voldeng 2001;Zhang et al 2007). Soybean cultivars of MG 000, 00, and 0 are the earliest in maturity and are mainly adapted to southern Canada.…”
Section: Field Experimentsmentioning
confidence: 99%
“…In the United States, a rating system has been developed, ranging from Group 00, in the northern region of the country, to Group VIII, in the southern region of the country [3]. The adaptation range of each American maturity group is between 200 and 300 km, following a north-south axis in the territory [4].…”
Section: Introductionmentioning
confidence: 99%